USE OF ELECTRONIC DIDACTIC TOOLS IN TEACHING FOREIGN LANGUAGES (Conferencea, 2023)
This article discusses the possibilities, importance, and tools of electronic didactic based on rapidly developing digital technologies in the educational system.